2017
DOI: 10.1016/j.jsxm.2017.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Pleasure and Function, Coital Trauma, and Sex Behaviors After Voluntary Medical Male Circumcision Among Men in the Dominican Republic

Abstract: Background Voluntary medical male circumcision (VMMC) is effective in decreasing the risk of HIV acquisition. As men resume sexual activity after circumcision, it will be important to study their satisfaction with the procedure, sexual pleasure and function, coital trauma, and risk compensation (RC), which can hamper or facilitate the long-term success of VMMC programs. Aim To assess men's satisfaction with VMMC, sexual pleas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 27 publications
3
19
0
1
Order By: Relevance
“…Each RCT found no adverse effect on any aspect of sexual function by the 2‐year post‐MC follow‐up point. Coital injuries were significantly lower in circumcised men …”
Section: Physical Harmmentioning
confidence: 87%
See 4 more Smart Citations
“…Each RCT found no adverse effect on any aspect of sexual function by the 2‐year post‐MC follow‐up point. Coital injuries were significantly lower in circumcised men …”
Section: Physical Harmmentioning
confidence: 87%
“…Evaluation of these identified multiple flaws . Other studies, including RCTs, found MC had no adverse effect. In fact, the RCTs found a net increase in sexual pleasure in men and their female partners.…”
Section: Physical Harmmentioning
confidence: 99%
See 3 more Smart Citations